Adaptation to metal toxicity: a comparison of hydrothermal vent and coastal shrimps - Maria Gonzalez‐Rey; Angela Serafim; Rui Company; Maria João Bebianno (Marine Ecology, 2007)
Rainbow vent field is one of the most metal‐contaminated hydrothermal sites on the Mid‐Atlantic Ridge near the Azores region. Two hydrothermal shrimp species dominate the fauna at the Rainbow site along with the mussel Bathymodiolus azoricus . Although the levels of essential and non‐essential metals in these shrimps have been studied, the biological consequences of a metal‐rich environment are still largely unknown. Therefore, the aim of this study was to determine the levels of metal‐binding proteins – metallothioneins (MT) and the activities of antioxidant enzymes – superoxide dismutase, catalase, total glutathione peroxidase and selenium‐dependent glutathione peroxidase in two hydrothermal vent shrimps ( Mirocaris fortunata and Rimicaris exoculata ) collected from the Rainbow site and to compare them with two coastal shrimps ( Palaemon elegans and Palaemonetes varians ) from a south Portugal lagoon (Ria Formosa) to evaluate their different adaptation strategies towards metals in their environment. Results show significant differences in MT levels and antioxidant enzymatic activities between vent and coastal shrimps and also between shrimp species collected from the same site. This suggests that biochemical responses in both vent and coastal shrimps are affected not only by the environmental characteristics but also by inter‐specific differences. Nevertheless, these responses apparently confer successful adaptation for survival in a metal‐extreme environment.